Experimental and Performance Analysis of Axial Jet Fan with Diffuser Angle 5° - Linn, Htet Htet; Swe, War War Min; Latt, Aung Ko; Kyaw, Sandar (The Indonesian Journal of Computer Science, 2026)
This study presents an experimental performance analysis of an axial jet fan with a converging nozzle and a 5° angle of diffuser, designed for basement car parking ventilation. The objective is to improve airflow quality and fan efficiency. The axial jet fan design parameters are computed with theoretical calculations and simulated computational fluid dynamics (CFD) the airflow characteristics and pressure distribution. The results were validated through experimental testing conducted in a fabricated tunnel. Parameters such as axial velocity, pressure distribution, and carbon monoxide (CO) concentration were measured at different fan speeds. The results indicate that the designed nozzle improves inlet airflow and diffuser pressure recovery, leading to improved fan efficiency. Additionally, CO concentration was significantly reduced over time, demonstrating effective ventilation performance. The study confirms that integrating nozzle–fan–diffuser components enhance operational efficiency of axial jet fan.